PENGARUH STRUKTUR MODAL DANSTRUKTUR KEPEMILIKAN TERHADAPFREE CASH FLOW SERTA DAMPAKNYA TERHADAP DIVIDEN (Studi Empiris Pada Perusahaan-Perusahaan Yang Go Public Di Bursa Efek Indonesia) - Iseu Anggraeni (AKURAT | Jurnal Ilmiah Akuntansi FE UNIBBA, 2017)
stock dividend indicates that the company is expressing confidence (confidents) towards its shareholders, but on the other hand the company does not pay dividends because the company is experiencing the benefit of cash or reason businesses gain retained earnings to do reinvestment. This study aims to determine how much influence the capital structure, the ownership structure of the free cash flow and its impact on the payment of dividends to companies that go public in Indonesia Stock Exchange. Samples were selected based on purposive sampling at companies that go public in Indonesia Stock Exchange 2000-2014 period which initiated the dividend year after an IPO to come by as many as 54 companies. This study used path analysis techniques. The result show that: 1) Capital Structure no effect on the Free Cash Flow; 2) Ownership structure significantly related to Free Cash Flow; 3) Capital Structure significant effect on dividend; 4) Ownership structure no effect on the dividend; 5) Free Cash Flow not effect on the dividend. Variable of free cash flow has reduced by dividends weakness in its calculations, it is suggested for further research, free cash flow is more relevant in this study are used for investment decisions.